New Plants for Florida: Stone Fruit - Richard L. Jones; Mary Duryea; Berry J. Treat; Wayne Sherman (EDIS)
Peach, nectarine, plum, apricot and cherry are called stone fruit because of their central hard pit. Because of Florida’s warm climate, breeding programs for stone fruit have focused on developing “low-chill” varieties – those that can grow and produce fruit with very few hours of chilling or cold weather in the winter. Florida’s low-chill stone fruit breeding program was initiated in the early 1950s and has succeeded thanks to two plant breeders, Ralph Sharpe and Wayne Sherman. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.